First description of a Raphidascaris species (Nematoda: Raphidascarididae) in a mudskipper Apocryptes bato (Actinopterygii: Gobiidae) from West Bengal, India. (12th August 2021) - Patra, B.K.; Choudhury, A.; Thorn, R.; Ash, A.
Abstract: A new nematode species, Raphidascaris mundeswariensis n. sp. (Raphidascarididae), is described from male and female specimens found in the intestines of the mudskipper Apocryptes bato (Hamilton, 1822) (Gobiidae) from the Mundeswari River of West Bengal, India. This species is distinguished from its congeners by 214–255-μm-long spicules, 14 pairs of preanal papillae of two markedly different sizes, one pair of adanal papillae, six pairs of postanal papillae and the absence of lateral alae. Phylogenetic analyses using partial sequences of the 28S ribosomal RNA gene place the new species in a clade containing Raphidascaris gigi, Raphidascaris lophii, Raphidascaris longispicula and two species of Hysterothylacium . The molecular analyses also corroborate results of previous studies that have found Raphidascaris and Hysterothylacium to be paraphyletic. The finding of R . mundeswariensis in A . bato is the first Raphidascaris species described from a mudskipper anywhere.